Evaluating Double Resampling through Simulation and Application in Semiparametric Truncated Spline for Waste Economic Value - Kamelia Hidayat; Adji Achmad Rinaldo Fernandes; Atiek Iriany; Moh. Zhafran Hidayatulloh (UIN Sumatera Utara, 2025)
This study developed a double resampling procedure as a method for estimating standard error in truncated spline semiparametric path modeling, given that standard error cannot be obtained analytically. Primary data were collected from 100 respondents through a Likert scale questionnaire and analyzed using a path structure involving Facility and Infrastructure Quality and Waste Bank Participation have a significantly positive effect on 3R-Based Waste Management Practices and the Waste Economic Value . The modeling process involved selecting knots, estimating spline functions, and evaluating double resampling performance through simulation studies. The results showed that and had a significant positive effect on and , while the relationship between and was negative before and after the 21% threshold. The simulation study shows that the Jackknife-Bootstrap method produces lower standard errors and bias, while the Bootstrap-Jackknife method is more stable at very small sample size. These findings confirm the effectiveness of double resampling.